Cholesterol-Induced Hepatic Inflammation Does Not Underlie the Predisposition to Insulin Resistance in Dyslipidemic Female LDL Receptor Knockout Mice. (28th February 2015) - Gruben, Nanda; Funke, Anouk; Kloosterhuis, Niels J.; Schreurs, Marijke; Sheedfar, Fareeba; Havinga, Rick; Houten, Sander M.; Shiri-Sverdlov, Ronit; van de Sluis, Bart; Kuivenhoven, Jan Albert; Koonen, Debby P. Y.; Hofker, Marten H.
Abstract : Chronic inflammation is considered a causal risk factor predisposing to insulin resistance. However, evidence is accumulating that inflammation confined to the liver may not be causal to metabolic dysfunction. To investigate this, we assessed if hepatic inflammation explains the predisposition towards insulin resistance in low-density lipoprotein receptor knock-out ( Ldlr −/− ) mice. For this, wild type (WT) and Ldlr −/− mice were fed a chow diet, a high fat (HF) diet, or a high fat, high cholesterol (HFC) diet for 2 weeks. Plasma lipid levels were elevated in chow-fed Ldlr −/− mice compared to WT mice. Although short-term HF or HFC feeding did not result in body weight gain and adipose tissue inflammation, dyslipidemia was worsened in Ldlr −/− mice compared to WT mice. In addition, dyslipidemic HF-fed Ldlr −/− mice had a higher hepatic glucose production rate than HF-fed WT mice, while peripheral insulin resistance was unaffected. This suggests that HF-fed Ldlr −/− mice suffered from hepatic insulin resistance. While HFC-fed Ldlr −/− mice displayed the anticipated increased hepatic inflammation, this did neither exacerbate systemic nor hepatic insulin resistance. Therefore, our results show that hepatic insulin resistance is unrelated to cholesterol-induced hepatic inflammation in Ldlr −/− mice, indicating that hepatic inflammation may not contribute to metabolic dysfunction per se.